Preposition Of Place Analysis As Linguistics Research In Twilight Saga: Breaking Dawn – Part 1 - larasati sekartadji; Farah Dita Yunia (Faculty of Education and Teachers Training, 2021)
This study will discuss the preposition of place in the novel Twilight Saga: Breaking Dawn - Part 1 which is known to be able to apply the proper use of the preposition of place in English. A preposition of place is a preposition that refers to a place in a sentence. The purpose of the preposition of place is to show the way the object of the preposition is against the subject or object of the sentence. The reason for choosing Twilight Saga: Breaking Dawn - Part 1 as the data source is because in this novel many sentences use prepositions to describe places. The results of the prepositions of place that appear from the identification of data in the novel Twilight Saga: Breaking Dawn - Part 1 include at, in, on. The most widely used preposition of place in this novel is